The crystal structure of 2-bromo-1,3-phenylene bis(4-methylbenzenesulfonate), C20H17BrO6S2 - Chen Jue-Yuan; Zou Long-Sheng; Lai Ni; Yin Zi-Yi; Yuan Lin; Li Zhong-Yan (Zeitschrift für Kristallographie - New Crystal Structures, 2023)
C20H17BrO6S2, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 8.173(2) Å, b = 8.256(2) Å, c = 16.514(5) Å, α = 89.947(3)°, β = 83.105(3)°, γ = 72.077(3)°, V = 1051.8(5) Å3, Z = 2, Rgt (F) = 0.0334, wRref (F 2) = 0.0889, T = 296(2) K.